Bio Simulators: a web UI for biological simulation - Pedersen, Michael; Oury, Nicolas; Phillips, Andrew (Bioinformatics, 2014)
A host of formal, textual languages for modeling cellular processes have recently emerged, but their simulation tools often require an installation process which can pose a barrier for use. Bio Simulators is a framework for easy online deployment of simulators, providing a uniform web-based user interface to a diverse pool of tools. The framework is demonstrated through two plugins based on the KaSim Kappa simulator, one running directly in the browser and another running in the cloud. Web tool: bsims.azurewebsites.net. KaSim client side simulator: github.com/NicolasOury/KaSimJS. KaSim cloud simulator: github.com/mdpedersen/KaSimCloud. michael.d.pedersen@gmail.com or Andrew.Phillips@microsoft.com. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.